SIGNATURES OF EXOCOMET ACTIVITY AROUND STARS AT DIFFERENT EVOLUTIONARY STAGES - Kuznyetsova, Y.; Pavlenko, Ya.; Kulyk, I.; Zakhozhay, O.; Korsun, P.; Borysenko, S.; Krushevska, V.; Shubina, O.; Andreev, M. (Одеські астрономічні публікації, 2020)
We discuss the current state of problems associated with the discovery and study of exocomets, i.e objects of extrasolar systems, that are in many aspects similar to the solar system comets. Thus far, more than 4,300 exoplanetary systems have been discovered, but little is known about the populations of subplanetary bodies in these systems, in particular comets. Existing theories of planet formation suggest that populations of small bodies in the planetary systems should be numerous, especially at the early stages of their formation. Currently, most of the stars observed with the confirmed transit exoplanets and candidate stars with exoplanetary systems have been collected in the Kepler and TESS space mi- ssion databases. These databases can be used for a search and study of the exocomet transit signatures in extrasolar systems. So far, the number of observed cases of exocomet transits has been small, only about 20 events. Due to the rapid accumulation of data, new researches aimed to identify the specific transit events and study the physical characteristics of small bodies in the extrasolar systems are of great importance.Worth considering is the concept of “falling evaporating bodies”, massive enough bodies surrounded by mini- atmospheres, which fall on the parent star. The events might produce the variable, short-time red-shifts of some spectral features in their spectra. Alternative evidence of exocomet transits can be obtained by detection of the cometary emissions in CO, C, and O lines in the millimeter region of the spectra of debris disks by the ALMA and APEX telescopes. We discuss the known detection methods based on the analysis of the photometric and spectral series of observational data of space missions and ground- based complexes. Some results of experimental studi- es of the exocometary transit signatures obtained by other authors are presented and discussed.